'Certainly the Muslim is the very devil incarnation': Islamophobia and The Merchant of Venice. (25th September 2018) - Awan, Imran; Issa, Islam
Abstract: In this paper, we examine Shakespeare's sixteenth‐century play, The Merchant of Venice . Anti‐Semitism is a key theme in this play. The well‐known central character, Shylock, is a Jewish man ridiculed and victimised because of his identity. Much literary research has been done on the anti‐Semitism of the play, and many social studies have compared anti‐Semitism and Islamophobia, but scarcely any research brings a Shakespearean play from the sixteenth century into the context of twenty‐first century Islamophobia. There are a number of similarities between the manner in which Shylock is ostracised and the current victimisation that Muslim communities are facing in Europe and more specifically the UK. With this in mind, we explore contextual and thematic elements of this play and argue that it is possible to apply the way Shylock is unfairly victimised on stage because of his identity as a Jew to the treatment of some Muslims today. In particular, the treatment he faces shares stark similarities with the types, impacts and consequences of Islamophobic hate crime today.